Neuroimaging selection for thrombectomy in pediatric stroke: a single-center experience. (16th May 2019) - Lee, Sarah; Heit, Jeremy J; Albers, Gregory W; Wintermark, Max; Jiang, Bin; Bernier, Eric; Fischbein, Nancy J; Mlynash, Michael; Marks, Michael P; Do, Huy M; Dodd, Robert L
Abstract : Background: The extended time window for endovascular therapy in adult stroke represents an opportunity for stroke treatment in children for whom diagnosis may be delayed. However, selection criteria for pediatric thrombectomy has not been defined. Methods: We performed a retrospective cohort study of patients aged <18 years presenting within 24 hours of acute large vessel occlusion. Patient consent was waived by our institutional IRB. Patient data derived from our institutional stroke database was compared between patients with good and poor outcome using Fisher's exact test, t-test, or Mann-Whitney U-test. Results: Twelve children were included: 8/12 (66.7%) were female, mean age 9.7±5.0 years, median National Institutes of Health Stroke Scale (NIHSS) 11.5 (IQR 10–14). Stroke etiology was cardioembolic in 75%, dissection in 16.7%, and cryptogenic in 8.3%. For 2/5 with perfusion imaging, Tmax >4 s appeared to better correlate with NIHSS. Nine patients (75%) were treated: seven underwent thrombectomy alone; one received IV alteplase and thrombectomy, and one received IV alteplase alone. Favorable outcome was achieved in 78% of treated patients versus 0% of untreated patients (P=0.018). All untreated patients had poor outcome, with death (n=2) or severe disability (n=1) at follow-up. Among treated patients, older children (12.8±2.9 vs 4.2±5.0 years, P=0.014) and children presenting as outpatient (100% vs 0%, P=0.028) appeared to have better outcomes. Conclusions: Perfusion imaging is feasible in pediatric stroke and may help identify salvageable tissue in extended time windows, though penumbral thresholds may differ from adult values. Further studies are needed to define criteria for thrombectomy in this unique population.